PEMODELAN TARIKAN PERJALANAN MAHASISWA DENGAN SEPEDA MOTOR - Mukhlis Mukhlis (TECHSI - Jurnal Teknik Informatika, 2013)
Transport mode used by students to the campus are public transport, private cars, motorcycles and walk. It is highly influenced by the distance of residence, travel time, travel expenses and family income. Based on samples obtained on 426 respondents that of respondents chose to use motorcycles and factors influencing it is the distance of residence and family income users. Trip attraction model by motorcycle is Y = 4,451 + 0,152 X1 + 0,040 X4. This models can be used as an alternative to solving transportation problems in Malikussaleh University in the future.